Characteristics, Genetic Mechanisms and Hydrocarbon Accumulation Control of Abnormal High Pressure in the Northwestern Qaidam Basin - Du, Xiaohua (Scientific Journal of Technology, 2026)
Abnormal high-pressure systems are widely developed within the Cenozoic strata of the northwestern Qaidam Basin (NW Qaidam), which is a key geological factor constraining hydrocarbon exploration and drilling safety. This study systematically investigates their distribution characteristics, genetic mechanisms, and controlling effects on hydrocarbon accumulation by comprehensively utilizing a large amount of geological, geophysical, and basin modeling data. The results indicate that the abnormal pressure in the NW Qaidam exhibits a four-segment vertical zonation: low pressure in shallow sections, normal pressure in middle sections, overpressure in mid-deep sections, and strong overpressure in deep sections. The top interface of overpressure lies between 1000 and 2500 m. On a planar scale, the overpressure centers are highly coupled with sedimentary centers. From the Upper Member of the Lower Ganchaigou Formation (E32) to the Upper Youshashan Formation (N22), the overpressure centers migrated eastward along with the sedimentary centers. Analysis of genetic mechanisms reveals that the overpressure in the study area results from the combined effects of undercompaction, tectonic compression, and hydrocarbon generation. The widely developed gypsum-salt rocks played a crucial indirect role in the formation and preservation of the overpressure system by enhancing sealing capacity and promoting organic matter enrichment and hydrocarbon generation. The evolution of abnormal high pressure is highly coupled with hydrocarbon charging episodes. The source-reservoir excess pressure difference (up to 10-20 MPa) provided the key driving force for hydrocarbon migration. The overpressure system itself constitutes an effective seal, forming an "overpressure compartment" together with the gypsum-salt caprocks. This compartment controls hydrocarbon accumulation and distribution, leading to primary high-pressure reservoirs within the compartment and secondary normal-pressure reservoirs outside it. This research deepens the theoretical understanding of overpressure systems in saline lacustrine basins under strong tectonic compression and provides a scientific basis for hydrocarbon exploration and drilling engineering safety in the NW Qaidam.